Dual-Carrier-Based PWM Method for DC-Link Capacitor Lifetime Extension in Three-Level Hybrid ANPC Inverters - Hakami, Samer Saleh; Halabi, Laith M.; Lee, Kyo Beum (IEEE Transactions on Industrial Electronics, 2023)
Power converters operate at varying low-, medium-, and high-voltage levels. Large electrolytic capacitors are usually used to sustain the associated dc-link current and stabilize the dc-link voltage. However, owing to different power converter applications, capacitors are affected by large ripples in the dc-link current, which increase heat exchange and reduce system reliability and lifespan. In this regard, this article proposes an innovative control technique for suppressing the ripple in the dc-link current and common-mode voltage (CMV) in hybrid active neutral point clamped inverters. The proposed control technique uses an improved dual-carrier-based pulsewidth modulation technique to create a new switching scheme by selecting the voltage vectors that contribute to the smallest ripples in the dc-link current according to each sector. Applying the proposed control technique significantly reduces the ripples in the dc-link current and CMV, which increases the reliability of the system and extends the lifetime of dc-link capacitors. The simulation and experimental results demonstrate the effectiveness of the proposed control strategy.
Keywords: Active neutral point clamped; Common mode voltage; Current ripples; Dc-link; DC-link capacitor; Hybrid active neutral point clamped; Inverter; MOS-FET; MOSFETs; Neutral-point clamped inverters; Common-mode voltage (CMV); current ripple; dc-link capacitors; hybrid active neutral point clamped (ANPC); leakage current; reliability